The Examination of the Popularity and Development of the CodeCup Team Competition - BLÉNESSY, GABRIELLA (Journal of Education, Technology and Computer Science, 2024)
International Informatics Olympiad in Teams (IIOT) is a competition for teams of high school students, organized since 2017. Hungary first participated in 2021. CodeCup, our national qualifier competition, gradually gained popularity over the past three years. In 2023–2024, teams have competed in four qualifying rounds. The goal of our research was to find means of increasing the number of competitors in CodeCup, and potentially in other national qualifier competitions as well. Primarily, we wanted to measure the effects of recent changes in the competition rules. We examined trends in the participation of the last three years: the list of involved schools, the age and gender distribution of students, with special regard to the impact of Program’Petition, a lightweight teer of CodeCup, launched in 2023. The results show that the number of schools has not changed significantly, but the number of competitors and the ratio of girls has increased.